Drought-induced Losses in Fruit Orchards - Gonda, István (Acta Agraria Debreceniensis, 2002)
Scientists investigating the causes of the extremities of climate that have become quite frequent in the Carpathian Basin over the past few years are quite often in doubts as to whether increased atmospheric warming and the shortage of rainfall are to be seen as recurrent natural phenomena under our climate, or the first signs of global warming. Climate anomalies have, to a certain extent, always been common in the Carpathian Basin. However, statistical data of the past few decades indicate that the rise in temperature and the fall in precipitation have, by now, become a tendency, which requires further in-depth scientific research.The series of articles to be published in continuation of this paper endeavors to synthesize the research results and many years of experiences, in order to give an analysis ofI. The economic effects and the symptoms of drought in tree culturesII. The possibilities of reducing the adverse affects of drought